TEACHERS' PERCEPTIONS TOWARDS THE USE OF AUTHENTIC MATERIALS IN EFL CLASSROOM : A Descriptive Qualitative Research of EFL Teachers'Perceptions at One of the Senior High Schools in Bandung - Ferlianty, Sinta (2016)
This research entitled Teachers' Perceptions towards the Use of Authentic Materials in EFL Classroom, aims to find out teachers' perceptions towards the use of authentic materials and teachers' difficulty in using authentic materials in EFL classroom. The participants of this study were two EFL teachers who taught XI graders in one of senior high schools in Bandung. The method used in this research was descriptive qualitative. This method allowed the researcher to analyze, categorize and interpreted the data. In describing the findings, descriptive method was also applied by attaching simple statistical data and charts. The data were gathered by conducting observation, giving Likert-scale questionnaire, and interviewing the participants. Based on the questionnaire classification scoring, the results indicated that one of the participants showed extremely positive responses and the rest gave positive perception category. The observation and interviews result showed that the participants also encountered obstacles in preparing and implementing authentic materials in the EFL classroom. To sum up, the use of authentic materials in EFL classroom might be challenging. To overcome this, the teachers should prepare the materials well by considering certain aspects in selecting suitable materials for instance students' needs, students' interests, and students' language proficiency. Keywords: teachers' perception, authentic materials, and EFL classroom Penilitian ini berjudul Persepsi Guru terhadap Penggunaan Authentic Materials di kelas EFL bertujuan untuk mengidentifikasi persepsi guru terhadap penggunaan authentic materials dan kesulitan yang dihadapi guru dalam menggunakan authentic materials di kelas EFL. Partisipan dari penelitian ini adalah dua orang guru yang mengajar Bahasa Inggris untuk siswa kelas XI di salah satu SMA di Bandung. Metode yang digunakan dalam penelitian ini adalah kualitatif deskriptif. Metode tersebut dapat memfasilitasi peneliti untuk menganalisa, mengkatogorisasi, dan menginterpretasi data yang diperoleh. Untuk mendeskripsikan hasil penelitian, penelitian ini menggunakan metode deskriptif dengan mencantumkan data statistik sederhana dan diagram. Pegumpulan data terhadap partisipan dapat diperoleh dengan menggunakan instrumen observasi, kuesioner Likert-scale, dan wawancara. Berdasarkan table klasifikasi peniliaian kuesioner, hasilnya satu dari dua partisipan menunjukkan respon sangat positif dan sisanya berada pad a kategori positif persepsi. Observasi dan hasil interview menunjukkan bahwa semua partisipan mengalami kendala dalam mengimplementasikan authentic materials di kelas EFL. Jadi, penggunaan authentic materials terhitung riskan. Untuk mengatasinya, guru harus merencanakan pembelajaran sebaik-baiknya dengan memperhatikan beberapa aspek penting dalam memilih materi yang cocok, antara lain kebutuhan siswa, ketertarikan siswa, dan tinggkat kemahiran berbahasa siswa. Kata Kunci: persepsi guru, authentic materials, dan kelas EFL